Synthesis and thermal decomposition kinetics of moisture curable polyurethane films as a reinforcing material for cultural relics - Xing Zhao; Liqin Wang; Lang Guo; Yanni Ma; Ziming Wang; Qing Niu; Liping Zheng (Scientific Reports, 2020)
Abstract In situ consolidation is the most common treatment to conserve cultural relics, but materials for preserving fragile organic cultural relics in humid archaeological excavation sites are scarce. To solve the problem, a moisture-curable polyurethane (MCPU) prepolymer was synthesized by reacting isophorone diisocyanate with polyethylene glycol 600. The standard acetone–dibutylamine method, Fourier transform infrared spectroscopy, gel chromatography and thermogravimetric analysis were utilized to determine the change in isocyanate groups before and after the reaction, the prepolymer molecular weight, the thermal decomposition kinetic parameters and the MCPU film lifetime. The results showed that the number-average molecular weight of the prepolymer was 749, and the weight average molecular weight was 1684. Isophorone groups in the prepolymer react with moisture in the air to form colorless, transparent, flexible films. The thermal decomposition of the MCPU films was a first-order reaction, and the decomposition process consisted of two stages. The Dakin equation was used to obtain the thermal aging equation lg t = 4600.82/T − 8.07, meaning that at 15 °C, the sample has an approximately 150-year lifetime. A new conservation material was developed, and its thermal decomposition kinetics were studied, which are significant for the conservation of fragile organic cultural relics in humid environments.